Chemical variables - lake from Stortjärn, platform, 2017-01-10–2025-06-10 - Svartberget Research Station (Swedish University of Agricultural Sciences, 2026)
Manual grab samples for chemical analysis are taken from the lake on a biweekly basis during ice-free conditions, and on a monthly basis during ice cover conditions. At the central lake sampling location water samples are collected from both epi- and hypolimnion during periods of stratification.
Svartberget Research Station (2026). Chemical variables - lake from Stortjärn, platform, 2017-01-10–2025-06-10 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/f8f3_22e1ztjX4VqsJob-nIr
Keywords: Svartberget Research Station; Lake; Time instant; Time instant; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; pH; pH; Specific conductivity; Specific conductivity; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrite-N/Nitrate-N; Nitrite-N/Nitrate-N; Sulphate-S; Sulphate-S; Fluorine; Fluorine; Bromine; Bromine; Chlorine; Chlorine; Aluminium; Aluminium; Boron; Boron; Calcium; Calcium; Iron; Iron; Potassium; Potassium; Magnesium; Magnesium; Manganese; Manganese; Sodium; Sodium; Phosphorus; Phosphorus; Sulfur; Sulfur; Silicon; Silicon; Zinc; Zinc; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap